2002
DOI: 10.1161/hh0402.105668
|View full text |Cite
|
Sign up to set email alerts
|

Lovastatin Enhances Ecto-5′-Nucleotidase Activity and Cell Surface Expression in Endothelial Cells

Abstract: Abstract-Extracellular adenosine production by the GPI-anchored Ecto-5Ј-Nucleotidase (Ecto-5Ј-Nu) plays an important role in the cardiovascular system, notably in defense against hypoxia. It has been previously suggested that HMG-CoA reductase inhibitors (HRIs) could potentiate the hypoxic stimulation of Ecto-5ЈNu in myocardial ischemia. In order to elucidate the mechanism of Ecto-5Ј-Nu stimulation by HRIs, Ecto-5Ј-Nu activity and expression were determined in an aortic endothelial cell line (SVAREC) incubated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
53
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(56 citation statements)
references
References 53 publications
3
53
0
Order By: Relevance
“…Recent reports have shown that statins have an attenuating role in CNS inflammation as demonstrated in the mouse EAE model [37] and by immunomodulatory effects on MS patient immune cells [38]. Interestingly, both pravastatin [39] and lovastatin [40] treatment leads to increased CD73 expression with tissue-protective effects. We speculate that increased CD73 expression and adenosine production might also be one mechanism whereby statin treatment leads to beneficial anti-inflammatory effects also seen in the treatment of autoimmune diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Recent reports have shown that statins have an attenuating role in CNS inflammation as demonstrated in the mouse EAE model [37] and by immunomodulatory effects on MS patient immune cells [38]. Interestingly, both pravastatin [39] and lovastatin [40] treatment leads to increased CD73 expression with tissue-protective effects. We speculate that increased CD73 expression and adenosine production might also be one mechanism whereby statin treatment leads to beneficial anti-inflammatory effects also seen in the treatment of autoimmune diseases.…”
Section: Discussionmentioning
confidence: 99%
“…This was demonstrated for lovastatin in rat endothelial cells, 10 pitavastatin in canine in vivo, 11 and atorvastatin in human vascular endothelial cells. 23 Our results support these previous findings and are the first to demonstrate this effect in a human in vivo setting.…”
Section: Rosuvastatin Increases Ecto-5-nucleotidasementioning
confidence: 71%
“…Inhibition of Rho may result in reduced endocytosis of CD73 and subsequently increased expression of CD73 on the cell membrane. 10 It has also been demonstrated that phosphatidylinositol 3-kinase and protein kinase C may influence CD73 activity by influencing its phosphorylation state and may thereby form an alternative route for statin-induced enhancement of CD73 activity. 11,24 Regardless of the underlying mechanism, activation of CD73 by statins is likely to contribute to the clinical efficacy of statins in a setting of cardiac infarction, because inhibition of CD73 attenuates the limiting effect of statins on infarct size in animals.…”
Section: Rosuvastatin Increases Ecto-5-nucleotidasementioning
confidence: 99%
“…We have previously shown in humans that activation of ecto-5'-nucleotidase mediates prevention of PS exposure by rosuvastatin after IR. The effect of statins on ecto-5'-nucleotidase appears to occur rapidly 6,7) . For example Sanada et al found a significant increase of ecto-5'-nucleotidase activity in dogs for different statins (pravastatin, pitavastatin and cerivastatin) already 10 minutes after treatment 7) .…”
Section: Discussionmentioning
confidence: 99%
“…Traditionally, this beneficial effect of statins has been explained by lowering of plasma cholesterol and sub-sequent reduced progression of atherosclerosis. Apart from its cholesterol lowering properties, statins have other ("pleiotropic") actions, such as up-regulation of ecto-5'-nucleotidase [5][6][7] , activation of the phosphatidylinositol 3-kinase-Akt pathway 8) and up-regulation of NO synthase 9,10) which all may increase tolerance against ischaemia and reperfusion (IR) [11][12][13] . Several animal studies have shown reduction of IR-injury as a result of statin treatment in both the heart and the kidney [14][15][16][17] .…”
Section: Introductionmentioning
confidence: 99%